2019
DOI: 10.1177/1557085119842660
|View full text |Cite
|
Sign up to set email alerts
|

Judges’ Gender and Sentencing in China: An Empirical Inquiry

Abstract: Although mixed results regarding judges’ gender disparity in sentencing have been uncovered globally by comparatists, China has yet to be considered. Based on documents of adjudication decisions collected from two cities, we examined district court judges’ sentencing decisions. Multilevel-multivariate analysis reveals negligible differences between male and female judges. We conclude that the similarities in the decision to incarcerate can be explained by the harmonious “Iron Triangle” relationship among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…The structure of the legal system is significant to gender difference. Wei and Xiong (2020) found there was no difference in the length of sentences awarded by women and men judges in China and there was little scope for difference to manifest. Sentencing guidelines limited judicial discretion, as did the 'Iron Triangle' of police, prosecution and court.…”
Section: Gender and Legal Professionsmentioning
confidence: 86%
“…The structure of the legal system is significant to gender difference. Wei and Xiong (2020) found there was no difference in the length of sentences awarded by women and men judges in China and there was little scope for difference to manifest. Sentencing guidelines limited judicial discretion, as did the 'Iron Triangle' of police, prosecution and court.…”
Section: Gender and Legal Professionsmentioning
confidence: 86%
“…For research on gender, law, and judging, this study is groundbreaking in two aspects: First, it reveals that in the Chinese criminal justice system, behavioral differences between male and female judges exist in the process rather than the outcome of judgment. The literature focuses solely on male and female Chinese judges’ differences in conviction and sentencing, without probing other working styles that can also settle disputes in criminal cases ( Wei & Xiong, 2020 ). Second, this research reveals male and female judges’ different understandings of the function of mediation.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese courts consider a wide range of severity indicators for sentencing sex offenses, such as the level of physical harmfulness, the level of social influence, the level of intrusiveness, number of victims, victims’ age, offense locations (private or public), and the number of offenders (SPC 2017). Previous studies also found that confounding factors (e.g., discretion, victims’ characteristics, judges’ characteristics, and territorial discrepancies) do not exert a significant effect in influencing sentence length for sex offending in Chinese jurisdictions (Wei & Xiong, 2020; Xia et al, 2019; Xiong et al, 2021). The negligible differences in sex offending sentencing in the Chinese courts have been attributed to two aspects: (1) the “Iron Triangle” (the relationships between the police, procuratorate, and court) poses a constraint for judges’ decision-making; (2) the directions for sex offending sentencing have been clearly instructed and regulated by the Criminal Law of People’s Republic of China and Sentencing Guideline, leaving little room for discretion (Wei & Xiong, 2020).…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies also found that confounding factors (e.g., discretion, victims’ characteristics, judges’ characteristics, and territorial discrepancies) do not exert a significant effect in influencing sentence length for sex offending in Chinese jurisdictions (Wei & Xiong, 2020; Xia et al, 2019; Xiong et al, 2021). The negligible differences in sex offending sentencing in the Chinese courts have been attributed to two aspects: (1) the “Iron Triangle” (the relationships between the police, procuratorate, and court) poses a constraint for judges’ decision-making; (2) the directions for sex offending sentencing have been clearly instructed and regulated by the Criminal Law of People’s Republic of China and Sentencing Guideline, leaving little room for discretion (Wei & Xiong, 2020). In this regard, the present study utilized one question “how long was your sentence by the court?” Responses ranged from 8 to 168 months (14 years).…”
Section: Methodsmentioning
confidence: 96%